DEVELOPMENT OF CRIMINAL LAWS REGULATING LIABILITY FOR ILLEGAL ABORTION IN LITHUANIA - Daukšaitė, Inga (Teisė, 2015)
Abortion was considered to be a crime already in the oldest sources of Lithuanian criminal law, the commitment of which was punished by certain penalties. The analysis reveals that penalties provided for by criminal laws to be imposed for the commitment of this crime gradually became more lenient. Furthermore, over time the legislator has withdrawn the woman’s criminal liability for termination of her own pregnancy. The latter alteration can be linked with the changed attitude towards abortion. For a long time, abortion was considered to be a sort of homicide – a crime by which it is attempted on the life of the foetus. Eventually abortion (specifically, illegal abortion) has become a crime by which it is attempted not on the life of the foetus, but which is endangering woman’s health and life.